PELAKSANAAN SUPERVISI KLINIS - Ishar Jhon Heri; Sudarwan Danim; Syaiful Anwar (Manajer Pendididikan, 2019)
The general research objective described how principal’s management in carrying out clinical supervision. While the specific purpose of this study is  (1) to describe how the principal as a supervisor in conducting professional teacher guidance , (2) to describe collegial relations between the principal as a supervisor and the teacher in clinical supervision, (3) to describe the principal way of supervisor and the teacher solve problems together, (4) to describe how to solve the problems faced by teachers. This research use descriptive qualitative method. Subject of the research that is principal, representative of the curriculum field and subject teachers. The result of research that principal’s management in carrying out clinical supervision has been running in accordance with existing procedures. As for the conclusion of this research is (1) the principal as a supervisor before conducting supervision activities has provided guidance, (2) the implementation of clinical supervision by the principal is clone by interacting with the teacher and creating collegial relationships, (3) the principal as a supervisor to be able to solve the problems faced by teachers , (4) the solution to the problem experienced by teacher is to create a cooperative relationship with the teacher in all activities in school.